Preferensi Wisatawan Nusantara Terhadap Komponen Wisata Papandayan Menggunakan Analisis Konjoin - Dini Turipanam Alamanda; Abdullah Ramdhan; Arif Partono Partono (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2020)
Garut Regency is known for its wealth of Mount tourism. Mount Papandayan Nature Parkis one of the most popular tourist attractions in Indonesia. Exploring tourist preferencesis an effort of the tourism object management to improve its marketing strategy. Thepurpose of this study is to analyse the preferences of mountain climbers who arenusantara tourists toward attractions of Mount Papandayan. Using quantitative methods,the survey was conducted by observation, interviews, and the distribution ofquestionnaires to 120 respondents. The data were then processed using conjoint analysistechniques and SPSS 20 software analysis tools. Interview results showed that there were7 attributes and 30 levels then were further analyzed. The SPSS output led to the resultsthat the nusantara tourist preferences of Mount Papandayan attractions are due to thebeautiful natural atmosphere, attraction of Menara Pandang photo spot, walkingactivities, having a tour guide when hiking, accessibility using motortaxi ‘ojek gunung’,and choosing a single ticket payment pattern for travel costs. The implications of thisresearch could be used as a consideration of the stakeholders of Garut mountain tourismin determining strategies and policies regarding sustainability tourism.